1,25-Dihydroxyvitamin D Inhibits Osteoarthritis by Modulating Interaction Between Vitamin D Receptor and NLRP3 in Macrophages - Duan A (Dove Medical Press, 2021)
Ao Duan,1,* Zemeng Ma,2,* Wanshun Liu,1,* Kai Shen,1,* Hao Zhou,1,* Shunbing Wang,3 Renyi Kong,4 Yuqi Shao,5 Yunzi Chen,2 Wei Guo,6 Feng Liu1 1Department of Orthopedics, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210029, Jiangsu, People’s Republic of China; 2Key Laboratory of Immune Microenvironment and Disease, Department of Immunology, Nanjing Medical University, Nanjing, 211100, People’s Republic of China; 3Department of Rheumatology and Immunology, Affiliated Hospital of Hospital of North Sichuan Medical College, Nanchong, 637000, People’s Republic of China; 4Department of Orthopedics, Xincheng Hospital of Traditional Chinese Medicine, Maanshan, 243131, Anhui, People’s Republic of China; 5Department of Orthopedics, The Second Affiliated Hospital of Xuzhou Medical University, Xuzhou, 221006, Jiangsu, People’s Republic of China; 6Department of Urology, The Affiliated Wuxi No.2 People’s Hospital of Nanjing Medical University, Wuxi, 214002, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Guo; Feng Liu Email weiguo_gavin@163.com; njliuf@163.comBackground: Osteoarthritis (OA) is the most prevalent chronic joint disease globally. Loss of extracellular matrix (ECM) by chondrocytes is a classic feature of OA. Inflammatory cytokines, such as interleukin-1β (IL-1β) and interleukin-18 (IL-18), secreted mainly by macrophages, promote expression of matrix degrading proteins and further aggravate progression of OA. 1,25-dihydroxyvitamin D (1,25VD) modulates inflammation thus exerting protective effects on cartilage tissue. However, the underlying mechanisms of 1,25VD activity have not been fully elucidated.Methods: The destabilization of the medial meniscus (DMM)-induced mice model of OA was established to investigate the protective effects of 1,25VD by micro-CT and Safranin-O and Fast Green staining. And the co-culture system between THP-1 cells and primary chondrocytes was constructed to explore the effects of vitamin D receptor (VDR) and 1,25VD on chondrogenic proliferation, apoptosis, and migration. The immunofluorescence staining and Western blot analysis were used to detect the expressions of ECM proteins and matrix degradation-associated proteases. Enzyme-linked immunosorbent assay (ELISA) was used to examine the expression levels of inflammatory cytokines.Results: The findings of the study showed that 1,25VD prevented cartilage degeneration and osteophyte formation by inhibiting secretion of inflammatory cytokines in OA mice model. These protective effects were exerted through the vitamin D receptor (VDR). Further studies showed that 1,25VD increased ubiquitination level of NLRP3 by binding to VDR, resulting in decrease in IL-1β and IL-18 secretion. These findings indicate that 1,25VD binds to VDR thus preventing chondrogenic ECM degradation by modulating macrophage NLRP3 activation and secretion of inflammatory cytokines, thus alleviating OA progression.Conclusion: Here, our study suggests that 1,25VD, targeting to VDR, prevents chondrogenic ECM degradation through regulating macrophage NLRP3 activation and inflammatory cytokines secretion, thereby alleviating OA. These findings provide information on a novel molecular mechanism for application of 1,25VD as OA therapy.Keywords: osteoarthritis, 1,25-dihydroxyvitamin D, vitamin D receptor, NLRP3, inflammatory cytokines